Analysis of the financial and economic activity agroturism - Daniela Ileana Godja (Dănilă) (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
This study presents the efficiency of tourism enterprises in the market economy, which is the essential condition of its existence. For this reason, economic and financial situation of the company is the basis of tourism taking all decisions and actions that commits additional expenses. Businesses in rural areas need to face some unique conditions that are not in urban areas. For this reason a need expanding business in rural tourism which is the result of creating favorable conditions for harmonization of elements rendered by: offer various types of accommodation; supply food products, traditional folklore, crafts and folklore; offer natural surroundings and environmental requirements; offer paid jobs in rural areas; infrastructural equipment in the public and private services. The impact of tourism on economic sectors is divided into a zone multiplier effects, and incentive plan output, income and employment.
Keywords: 330; tourism; economy; economic resources